Islamic Work Ethics, Organizational Culture and Organizational Commitment: A Study of Employees at Majlis Amanah Rakyat - Nor Nazliyah, Zainol (2009)
The purpose of this study was to review the relationship of Islamic Work Ethic,Organizational Culture and Organizational Commitment among staff in MARA Perlis and Kedah. This study due to the lack of previous study regarding both Islamic Work Ethics and culture on commitment especially in Malaysia environment. From this study,Islamic work ethics and organizational culture were measured to prove whether they can influence employees’ commitment towards their organization. Questionnaire contain of four (4) sections which are demographic characteristic, Islamic work ethics,organizational culture and organizational commitment. The data analyzed by using SPSS 12 and Structural Equation Modeling (SEM) via AMOS version 4.